180 to 240 GHz broadband, EM‐based power amplifier using 0.5‐μm InP DHBT technology. (8th March 2019) - Li, Yukun; Zhang, Yong; Li, Xiao; Chen, Yapei; Cheng, Wei; Sun, Yan; Lu, Haiyan
Abstract: This paper reports a power amplifier (PA) terahertz monolithic integrated circuit (TMIC) from 180 to 240 GHz. This amplifier is fabricated from a 0.5‐μm indium phosphide double heterojunction bipolar transistor (InP DHBT) technology, jointly with a thin‐film microstrip wiring environment. Furthermore, an electromagnetic (EM) simulation method is proposed for the parameter extraction of InP DHBTs and amplifier design. This five‐stage amplifier has >6.1 dB S 21 gain from 180 to 240 GHz, peaks 10.4 dB S 21 gain at 210 GHz. At 213 GHz operation, the saturated output power is 5.8 dBm with 7.3 dB large‐signal gain, and this amplifier occupies 2.52 mm 2 including pads.